Financing Strategy Of Refuse Derived Fuel (Rdf) Plant Based On Investment Project Analysis (Case Study Cilacap RDF Plant) - Reni Romaulina; Taufik Faturohman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Refused Derived Fuel (RDF) is a waste processing method that can be used as co-firing in the cement industry. Currently, the Cilacap RDF Plant is one of the RDFs successfully operating in Indonesia, with a machine capacity of up to 200 tons/day. This success has encouraged many local governments to build RDF facilities to handle waste. The research aims to propose alternative funding scenarios for the development of RDF so that it can be applied in other places. Not all regions have the same opportunities as RDF Cilacap, where investment financing includes the construction of RDF facilities and machinery covered by many stakeholders. This study also calculates the potential for reducing CO2 emissions with the RDF plant and estimates the potential carbon trading value from the reduction in CO2 emissions. The analysis method in alternative scenario studies uses investment project analysis such as Discounted Cash Flow (DCF), NPV, IRR, Profitability Index, Payback Period, Discounted Payback Period, and IPCC 2006 to calculate CO2 emission reductions. The potential for reducing CO2 emissions in this study is calculated by comparing the value of CO2 produced if waste is disposed of in a landfill (open dumping) and the waste is processed into RDF. The research results show that the third scenario is suitable and feasible for regions planning to build an RDF Factory. It is recommended that the Central Government bear the responsibility for the RDF Factory building infrastructure and the investors or third parties take responsibility for the machinery. The potential for reducing CO2 emissions with the existence of the RDF Plant Cilacap for 20 years is 231,944.86 tons. If multiplied by the average price in the secondary market, IDR 69,600 (USD 4.45), the potential for obtaining funds is IDR 16,143 million, or equivalently, we calculate it in present value to IDR 5,284 million.